May COVID-19 outbreaks lead to a worsening of skin chronic inflammatory conditions?. (October 2020) - Marasca, Claudio; Ruggiero, Angelo; Napolitano, Maddalena; Fabbrocini, Gabriella; Megna, Matteo
Abstract: The emergence of the novel beta Coronavirus has raised serious concerns due to the virus rapid dissemination worldwide. Many areas throughout the world are now experiencing the COVID 19 outbreaks with government and policy authorities taking many aggressive isolation or restriction measures, drastically reducing also patient's visits and limiting only to the most urgent ones such as oncological visits or emergencies. Several studies have demonstrated a relationship between increased weight, obesity, diabetes, hypertension and inflammatory skin diseases. Furthermore, weight loss interventions have been shown to improve psoriasis, as well as hidradenitis suppurativa, and increase responsiveness to treatment of this conditions. We suppose that due to aggressive isolation or restriction measures, in the next future dermatologist will face with a common worsening of chronic skin inflammatory conditions due to reduced physical activities, increased intake of calories with the derived increase body weight and always more frequent treatment discontinuation. It is time to start potential preventive strategies which could limit the expected negative impact of COVID-19 related quarantine on skin diseases.